Complications of Parotid surgery: A study in 60 cases - Atikuzzaman, Kazi; Rahman, Mushfiqur; Yasmeen, Naseem (Bangladesh Journal of Otorhinolaryngology, 2021)
Objective: To evaluate the common complications following parotid surgery. Material & methods: A retrospective study was done from January 2011 to December 2019 in the Department of ENT & Head Neck Surgery, Enam Medical College & hospital, Savar. Sixty (60) patients with both benign & malignant parotid disease underwent surgical treatment was selected for this study. All cases were diagnosed preoperatively by Fine Needle Aspiration Cytology (FNAC). Patients with preoperative facial nerve palsy were excluded from this study. Patients were followed up for six months and per operative & postoperative complications were evaluated. Results: Out of 60 patients, superficial parotidectomy was done in52 (86.67%) patients and total conservative parotidectomy was done in 08 (13.33%) patients. In this study 56 cases were benign and 04 cases were malignant. Among this 41 (68.33%) pleomorphic adenoma, 05 (8.33%) warthin’s tumour, 03 (5%) benign lymphoepithelial cyst, 03(5%) haemangioma, 02(3.33) sialocele, 01(1.67) dermoid and 01 (1.67%) had salivary fistula. All 04(6.67%) malignant cases were diagnosed as mucoepidermoid carcinoma. Majority of pleomorphic adenomas (92.68%) involved the superficial lobe of the gland. Most commonly observed post operative complication was facial nerve paresis (05%), but only 1.67% developed permanent palsy. Others complication includes Hypoesthesia of the greater auricular nerve (05%), Frey’s syndrome (3.33%) & wound infection (3.33%). Conclusion: Facial nerve palsy is the frequent complication after parotid surgery in this study. Surgeons have to pay attention to minimize the risk of complication during parotidectomy. However, this operation continues to be a challenge on account of the wide range of tumours encountered and the variations in size and location and the facial nerve preservation. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 59-65